2018
DOI: 10.1051/metal/2017103
|View full text |Cite
|
Sign up to set email alerts
|

Influence of B2O3on viscosity and structure of low MgO slag containing titanium

Abstract: The viscous behavior of CaO–SiO2–15.2 wt% Al2O3–4.8 wt% MgO–TiO2–B2O3 slags is studied. The effect of the TiO2 and B2O3 on the viscosity and apparent activation energy, as well as the effect of B2O3 on structure is investigated through Raman spectroscopy. The viscosity and apparent activation energy of CaO–SiO2–15.2 wt% Al2O3–4.8 wt% MgO–TiO2 are decreased with increased TiO2 content, which can be explained by the network modifier role that TiO2 acts in slags. The addition of B2O3 can reduce the viscosity of C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 21 publications
1
15
0
Order By: Relevance
“…It can be found that the viscosity increased with the rise in B 2 O 3 content, in contrast to the experimental results shown in Figure 11. As reported in the literature [10,17], this interesting phenomenon is worthy of investigation to understand the difference between FactSage calculation results and experimental measurement results. trihedral units replace complicated silicate network units, resulting in the viscosity decreasing [11,25,26].…”
Section: Effects Of B 2 O 3 On Break Temperature and Apparent Activatmentioning
confidence: 69%
See 2 more Smart Citations
“…It can be found that the viscosity increased with the rise in B 2 O 3 content, in contrast to the experimental results shown in Figure 11. As reported in the literature [10,17], this interesting phenomenon is worthy of investigation to understand the difference between FactSage calculation results and experimental measurement results. trihedral units replace complicated silicate network units, resulting in the viscosity decreasing [11,25,26].…”
Section: Effects Of B 2 O 3 On Break Temperature and Apparent Activatmentioning
confidence: 69%
“…Most of these phases were identical to the results of Figure 5, implying that the prediction of FactSage was convincing. It was also found that the slag structure initially became complicated and then gradually changed into a simple structure with the phase transformation caused by the addition of B2O3 [17].…”
Section: Effects Of B2o3 On Phase and Mct Of Cao-sio2-feox-mgo Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…26,27 The effect of B 2 O 3 con-tent on the viscosity and structure of silicate-based slags was studied in the past. [26][27][28][29][30][31][32] Sadaf et al 26 investigated the viscosity and crystallization behavior of (45 − 0.556x) CaO-(36 − 0.444x) SiO 2 -(4 + x) B 2 O 3 -4 Al 2 O 3 -8 Na 2 O-2 MgO-Li 2 O slag at 1300 • C. No crystallization phenomenon was observed when B 2 O 3 content exceeded 6 wt.%. Although the increase of B 2 O 3 content improved the degree of polymerization (DOP), it reduced the provided percentage of silicate unit in the melt due to the increase of [BO 3 ] unit.…”
Section: Introductionmentioning
confidence: 99%
“…Similar phenomena were found by some other researchers. 27,29,30,31 [BO 3 ] convert to [BO 4 ] by binding with free oxygen (FO, O 2− ), where [BO 4 ] can randomly attached to [SiO 4 ]. This leads to the depolymerization of the silicate network, which can be reflected by the amount of nonbridging oxygen (NBO, O − ) in the melt.…”
Section: Introductionmentioning
confidence: 99%